2020
DOI: 10.1016/j.foodcont.2019.106963
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic microbial interactions between lactic acid bacteria and yeasts during production of Nigerian indigenous fermented foods and beverages

Abstract: Fermented foods and beverages are mainly consumed by the indigenous people of Africa and other developing countries. Traditional fermentation is an age-long means of preserving perishable foods especially when other methods of preservation are not available and/or not consistent. The main beneficial microorganisms that are responsible for the fermentation of African indigenous fermented foods and beverages are lactic acid bacteria and yeasts which may be present as microflora on the substrates or added as star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 61 publications
0
21
0
1
Order By: Relevance
“…It is possible that the moisture-permeable bag in DWA provided a flourishing environment that could allow microbial growth, as indicated with the high microbial count in DWA loins in the current study. It has been suggested that LAB have a symbiotic relationship with aerobic bacteria and yeast to promote fermentation (Horiuchi and Sasaki, 2012;Adesulu-Dahunsi et al, 2020) and thus potentially decrease the product pH due to acid production.…”
Section: Processing Loss and Saleable Yieldmentioning
confidence: 99%
“…It is possible that the moisture-permeable bag in DWA provided a flourishing environment that could allow microbial growth, as indicated with the high microbial count in DWA loins in the current study. It has been suggested that LAB have a symbiotic relationship with aerobic bacteria and yeast to promote fermentation (Horiuchi and Sasaki, 2012;Adesulu-Dahunsi et al, 2020) and thus potentially decrease the product pH due to acid production.…”
Section: Processing Loss and Saleable Yieldmentioning
confidence: 99%
“…The beneficial outcomes of controlling microorganisms are mirrored in product safety, increased shelf life, improved nutrient contents and availability, palatability, and enhanced sensory traits. For example, it was shown that S. cerevisiae improves LAB growth by transmitting essential metabolites, such as pyruvate, amino acids, and vitamins, while it uses some metabolites produced by LAB as carbon sources [150]. Moreover, Salari et al concluded in their study that malt and L. delbrueckii were the best substrate and lactic strain for producing a functional beverage with the highest cell viability (1.2 × 10 6 cfu/mL after 4 weeks) [151].…”
Section: Fermentation Microbiota and Safety Of Nfcbsmentioning
confidence: 99%
“…Finalmente, se logró demostrar la importancia de los diferentes grupos microbianos y el efecto que su presencia pueda tener en los productos terminados. De hecho, se observó el efecto que tiene la concomitancia de BAL y levaduras en la cual las primeras favorecen la acidificación del masato, lo que ayuda el crecimiento de las levaduras que a su vez brindan nutrientes para el crecimiento de las BAL (Adesulu-Dahunsi et al, 2020;Lacerda et al, 2010). Igualmente se ve como los microorganismos afectan las características fisicoquímicas propias del producto.…”
Section: Resultados Y Discusiónunclassified